Loads on hydraulic engineering and berthing structures of the coastal zone of the Neva Bay - Kozinetc Galina; Badenko Vladimir; Sharapov Dmitry; Shonina Ekaterina (Magazine of Civil Engineering)
The object of the research is the hydraulic structures in the Neva Bay, including ports, dams, and navigation facilities, which are subjected to natural loads such as ice, wave, wind, and water level fluctuations. The study focuses on analyzing the impact of these forces on the stability and safety of these structures. The research is of high relevance due to the increasing challenges posed by climate change, which alters hydrological and ice conditions, and the growing human activity in the region that places additional pressure on the bay's ecosystem and infrastructure. The analysis of natural loads is crucial for the design of resilient structures that can withstand extreme weather events and maintain safe operations in the Neva Bay. The goal of the research is to assess the natural loads on hydraulic structures in the Neva Bay, providing reliable calculation methods for their impact. The tasks include analyzing the ice regime, wave and wind loads, and utilizing modern modeling techniques to develop optimal design solutions for these facilities. The results demonstrate that ice and wave loads significantly affect the safety of hydraulic structures in the Neva Bay, and appropriate measures, such as protective piers and icebreaker assistance, can mitigate these impacts. The research provides valuable data for the design of durable and resilient infrastructure in the region, accounting for the specific natural conditions of the Neva Bay.